Pengaruh Fraud Pentagon Dan Tingkat Suku Bunga Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Consumer Cyclicals Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Risna Maulani; Yana Mustika; Sopian Sopian (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the effect of fraud pentagon and interest rate levels on financial statement fraud in consumer cyclical companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Fraud pentagon, which consists of pressure, opportunity, rationalization, capability, and arrogance, is the main focus to see how each element affects the potential for fraud in the company's financial statements. Interest rates are also analyzed as external variables that can contribute to financial pressure and encourage fraudulent behavior. The method in this study uses quantitative analysis. This study uses a purposive sampling technique to select samples, so that 12 consumer cyclical companies were obtained with a research period from 2020-2022. The data analysis technique applied is multiple linear regression, with hypothesis testing using the T-test, F-test, and coefficient of determination, all carried out using SPSS software version 26. The results of this study indicate that, overall, the variables External Pressure, Nature of Industry, Change of Director, and interest rates have a significant effect on financial reporting fraud in consumer cyclical companies listed on the Indonesia Stock Exchange during the 2020-2022 period. However, a separate analysis shows that the variables Change in Auditor and Frequent Number of CEO's Picture (CEOPIC) do not show a significant effect on financial reporting fraud in these companies during the same period.